Enhancing Students' Reaction Writing via Short Stories: A Pedagogical Perspective - Omar, Ainon; Marini Mohd. Ghazali, Ezatul (Indonesian Journal of EFL and Linguistics, 2016)
Studies have shown that literary texts such as short stories have been able to develop students’ interpretative skills as well as provide opportunities for students to enhance their critical thinking skills. This study aimed at investigating the use of short stories on enhancing students’ reaction writing. The purpose of the study was to look into a new method that can assist students in expressing their views and opinions about current issues. Thus, a study was conducted to investigate whether the use of short stories as an authentic material can assist students in enhancing their reaction writing. An experimental study was employed on a group of technical students. A pre-test was administered followed by treatment sessions and finally a post-test before a semi-structured interview was conducted on lecturers. The study gathered data on the lecturers’ perceptions towards the idea of incorporating literary texts in their English language lessons. The findings showed that the use of the short story had assisted students to generate ideas to write their reaction paper although a lot of guidance had to be given by the lecturer. The students as well as the lecturers were optimistic on the idea of incorporating literature in the English language course. However, the choice of literary texts needs to be carefully selected and also students’ interests and needs are taken into consideration in order for them to write their reaction paper.